Energy Crossover from Leader to Followers : A Time-lagged Study of the Effects of Energy Discrepancy and Leader-Member Exchange - Parent-Rocheleau, Xavier, (Colegio Oficial de Psicólogos de Madrid, 2020)
This study investigates the effects of the difference between leaders' and followers' level of subjective energy on the change in subordinates' energy one year later, and on customer-oriented citizenship behaviors. Building mainly on the crossover model, our time-lagged model also examines the moderating role of leader-member exchange. Results of polynomial regression and response surface analyses performed with a sample of 277 dyads in the retail sector indicate that the effect of the energy gap is asymmetrical, such that followers paired with a more energetic leader gain energy one year later, whereas those matched with less energetic leaders experience energy depletion. As expected, a high-quality relationship buffers the de-energizing effect of leaders with lower energy and augments the gain of energy triggered by more energetic leaders.